EFFECTS OF STRATEGIC MANAGEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE OF HORN OF AFRICA UNIVERSITY IN SOMALIA - DHUBOW NOOR, AHMED; THEURI, FRIDAH (IJRDO - Journal of Business Management, 2016)
The purpose of this project was to examine the effects of strategic management practices on organizational performance of Horn of Africa University in Somalia. The main purpose of the study was to cover the limitations in such companies in reaching the organizational performance because there little understand and lack of past study in such area Mogadishu universities having. So implementing such study the researcher presented strategic, financial and regulatory policy management as listed questionnaires for solving the research problem for institution managers is implementation of strategies. University performance may be assessed using a number of measures and aggregate measures of performance can be derived in terms of the connections between university outputs and/or inputs and national competitiveness. In some respects this measure is highly insightful in that it serves to illustrate the connection between university performance and national socio-economic development potential. This was supported by recent research studies indicating that most big organizations have had problems in implementing their strategies and in many occasions have failed in service delivery. .The study employed a descriptive method which is can provide and give layout of the finding to the research and also population of the study which as lecturer of the university the researcher was to conduct through administration of questionnaires. Data was collected from a sample of 49 person of the Horn of Africa University using purposive sampling technique. Both descriptive and inferential statistics was used to analyze data with the help of Statistical Package for Social Scientists (SPSS) version 22.0.